2005
DOI: 10.1097/01.sla.0000179622.37270.36
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Perioperative Adjuncts During Minimally Invasive Parathyroidectomy

Abstract: This series is one of the largest to date that prospectively compares the use of sestamibi scanning, radioguided surgery, and ioPTH testing. Of all the perioperative adjuncts used during parathyroid surgery, ioPTH testing has the highest sensitivity, positive predictive value, and accuracy. Thus, the inherent variability of sestamibi scanning and radioguided techniques emphasizes the critical role of ioPTH testing during parathyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 26 publications
5
148
1
Order By: Relevance
“…A study by Sosa et al [58] demonstrated that surgeon experience determined the length of stay and number of complications and that hospital volume was not consistently associated with outcomes. If undertaken by an experienced endocrine surgeon, minimally invasive parathyroidectomy is an ideal operation if preoperative imaging localizes an adenoma, otherwise bilateral neck exploration is undertaken [59].…”
Section: Surgicalmentioning
confidence: 99%
“…A study by Sosa et al [58] demonstrated that surgeon experience determined the length of stay and number of complications and that hospital volume was not consistently associated with outcomes. If undertaken by an experienced endocrine surgeon, minimally invasive parathyroidectomy is an ideal operation if preoperative imaging localizes an adenoma, otherwise bilateral neck exploration is undertaken [59].…”
Section: Surgicalmentioning
confidence: 99%
“…Therefore investigators have tried to identify acquisition schemes by using a combination of unenhanced and multiple postcontrast phases including 2 [25][26][27] with the time interval ranging from 30 to 90 seconds, each with strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…1 Definitive treatment requires surgical excision, and preoperative localization with imaging is commonly used to decrease the size of surgical incisions and complication rates. 2 Imaging has been increasingly used for preoperative detection of parathyroid adenomas. While sonography and technetium Tc99m sestamibi scintigraphy have often been used as first-line imaging to localize PTA, these tests are often inconclusive.…”
mentioning
confidence: 99%
“…The success of MIP can be improved with techniques such as radioguidance and intraoperative PTH (ioPTH) monitoring that confirm the intraoperative localization of abnormal glands (27). A radioguided parathyroidectomy involves preoperative intravenous injection of technetium-99m sestamibi 1-2 hours prior to the operation and use of a handheld gamma probe intraoperatively to localize hyperfunctioning parathyroid glands.…”
Section: Parathyroidectomymentioning
confidence: 99%